2008
DOI: 10.1002/hbm.20574
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aging on cerebral blood flow, oxygen metabolism, and blood oxygenation level dependent responses to visual stimulation

Abstract: Calibrated functional magnetic resonance imaging (fMRI) provides a noninvasive technique to assess functional metabolic changes associated with normal aging. We simultaneously measured both the magnitude of the blood oxygenation level dependent (BOLD) and cerebral blood flow (CBF) responses in the visual cortex for separate conditions of mild hypercapnia (5% CO 2 ) and a simple checkerboard stimulus in healthy younger (n = 10, mean: 28-years-old) and older (n = 10, mean: 53-years-old) adults. From these data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
182
2
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 197 publications
(208 citation statements)
references
References 66 publications
17
182
2
1
Order By: Relevance
“…A number of studies (33,34) have shown that increases or decreases in BOLD response between young and old individuals could easily arise as artifacts of basal state factors such as metabolic rate and neurovascular coupling. With this caveat in mind, testing a main effect of group would have been difficult to interpret (this difference was sig- Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies (33,34) have shown that increases or decreases in BOLD response between young and old individuals could easily arise as artifacts of basal state factors such as metabolic rate and neurovascular coupling. With this caveat in mind, testing a main effect of group would have been difficult to interpret (this difference was sig- Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8][9][10] Advanced neuroimaging methods, such as calibrated fMRI, coupled with diverse task paradigms to evoke neural activity in different ROIs, could be employed to test this hypothesis. [16][17][18][19]21,79 MS-related alterations to functional hyperemia could also influence measurement of the temporal associations used to estimate functional connectivity at rest and during tasks. 51,80,81 MS involves changes in task and resting-state functional connectivity relative to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…60 An alteration in the normal relationship between CBF and CBV after TBI could result in a decrease in the amplitude of the PSU. 21 Reductions in CBF as a function of age, however, have not directly translated into a reduction in the BOLD PSU, 61 suggesting that other mechanisms such as a decrease in the number/width of microvessels 40 and/or alterations in vasocompliance after injury may also be contributing factors. Moreover, the exact spatial locations of the reductions in CBF are likely to be dependent on initial biomechanical injury forces, which are variable across individual patients.…”
mentioning
confidence: 99%